Intrascrotal Collection in an Acute Pancreatitis: A Case Report and Review of the Literature - L. Moens; P. Yengue Yengue; C. Assenmacher (Case Reports in Urology)
Context. An inguinoscrotal swelling occurring during an acute pancreatitis is very rare. Case Report. We report a case of right inguinoscrotal swelling appearing in connection with an interstitial edematous acute pancreatitis. We have noticed a spontaneous complete reduction of the right inguinoscrotal swelling after 10 days. Conclusion. The management of a scrotal swelling should be the least invasive possible method but also the most complete possible method to avoid unnecessary interventions. The exclusion of a pathology that could affect the vital prognosis of the testis remains the absolute priority. An acute scrotum swelling must be carried out by the clinical management by a professional and must be completed with an ultrasonography of the scrotum. Despite all that, if the original etiology of the acute scrotum remains unknown, an abdominopelvic CT scan could provide more details and so could offer a different diagnosis of exclusion, different from the diagnosis of acute idiopathic scrotal edema (AISE). This rare complication of acute pancreatitis reported could be mistaken for a more common pathology. If that complication is identified, it will not require a surgical intervention if there is a correct management of the acute pancreatitis which could justify a broader CT scan.